Balancing the Effectiveness and Costs of Immune Checkpoint Inhibitors in Advanced Cancer - McKenna, Michael (Trinity Student Medical Journal, 2020)
Conventional cancer therapeutics, while having transformed the survival of patients diagnosed with early stage cancer, have failed to produce similar results in patients diagnosed with more advanced cancer. It is for this reason that the arrival of immunotherapy has generated such a visceral interest in the field of oncology. Labelled ‘Breakthrough of the Year’ by Science in 2013, the field of immunotherapy has continued to grow exponentially, and promising preclinical results have translated into efficacious results in clinical trials, particularly in patients with end-stage disease. This has culminated in an ever-growing list of approvals for agents which have been designed to harness the power of the immune system. Immune checkpoint inhibitors in particular are regarded as potent new tools in the cancer therapeutics arsenal and have produced remarkable results in clinical trials in various cancer types. However, in the context of their increasing use in combination therapy and their remarkably high cost:benefit ratio, it must be asked whether these immune checkpoint inhibitors are a realistic solution to an ever increasing cancer burden. Is their price just a little too steep to pay?